2015
DOI: 10.17096/jiufd.98462
|View full text |Cite
|
Sign up to set email alerts
|

Should the Teeth in the Line of Jaw Fractures Be Extracted?

Abstract: Fractures in the jaw bones could present themselves differently according to the strength of the force and the bone’s ability to absorb the impact. The location and type of the fracture is important as well as the cause of the fracture (traffic accidents, melee trauma, pathologic changes). Pre-existing pathologic lesions, position of the teeth and the way they are affected by the fracture have a great influence on the prognosis. Whether to extract the teeth in the line of a fracture has always been controversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Extraction of any de-vital teeth in the line of fracture and debridement of any necrotic soft and hard tissue and restabilization of the fracture must occur. 20,21 In most instances, especially those that are long-standing fibrous unions, bone grafting will be necessary to effect osseous union . The fragments must be exposed and cleaned of any fibrous tissue.…”
Section: Fibrous Union/nonunionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of any de-vital teeth in the line of fracture and debridement of any necrotic soft and hard tissue and restabilization of the fracture must occur. 20,21 In most instances, especially those that are long-standing fibrous unions, bone grafting will be necessary to effect osseous union . The fragments must be exposed and cleaned of any fibrous tissue.…”
Section: Fibrous Union/nonunionmentioning
confidence: 99%
“…One must consider the design of the flap anytime an extraction is planned to allow for adequate coverage of the hardware used. 20,21 According to Chrcanovic, tooth buds in the line of pediatric mandibular fractures should not be removed or replaced in the (alleged) proper position despite the degree of displacement, as studies showed that even tooth buds in the early stage of calcification and those involved in widely displaced fracture sites continued development and erupt. 22 Intact teeth should also be left in situ if they show no evidence of severe loosening or inflammatory change.…”
Section: Infectionmentioning
confidence: 99%
“…10,14,15 The review of the literature favours the conservative approach for teeth in the line of fracture. 16 Many previous studies have suggested that any source of infection corresponding to fractures should be eliminated as it may cause delayed union or non-union of the fracture 7,9,10,18 or it may increase the chances of complications such as osteomyelitis. 3 Retained teeth, even if healthy, were usually removed, as such teeth usually caused infection in the fracture line.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a tooth in the fracture line may increase bone fragment movement and consequently increase the risk of infection. Extracting the tooth from the fracture line increases the surface between bone fragments, and the open socket becomes a large bacterial pathway. Thus, it may complicate the immobilization of fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation